Formation of the flow of failures in antifriction systems - Кульгавый, Э.А. (Problems of Tribology, 2014)
Flow rate of failures in the tribological system determines the tribological properties of the structures of the dissipative type that are formed during burnishing. Phasing associated with partial and reversible disruption of these structures has arisen due to this deterioration. Sudden failures are the result of irreversible destruction tribostruktures that leads to the seizure, jamming, breakage, etc. In this paper the mechanism and patterns of development failures due to wear and sudden failures.